Knowledge-driven digital innovation in supply chains: An organizational perspective - Lu XiaoWen; Taghipour Atour (Journal of Innovation & Knowledge)
In response to rising complexity and dynamic challenges in supply chains, digitalization has emerged as a key innovation to enhance organizational competitiveness. This study develops a multidimensional theoretical framework by integrating five foundational management and organizational theories to explore how organizations adopt digital transformation from a knowledge-driven perspective. The concept of Perceived Digitalization Impact (PDI) is introduced to capture how organizations evaluate the strategic and knowledge value of digitalization. Based on 202 survey responses and tested through structural equation modeling, the results show that supply chain management objectives, operational difficulties, and decision-making levels significantly shape PDI, which strongly influences the adoption of additional digital tools. The findings contribute to innovation and knowledge literature by shifting the analysis of adoption behavior from individuals to organizations and offering practical guidance for aligning digital initiatives with internal priorities and resource availability. They highlight the central role of perceived digital value in enabling adaptive and knowledge-informed innovation, and improving supply chain competitiveness.